Advanced mechanics of continua - Surana, Karan S. (Boca Raton : CRC Press, 2014)
'In a unified treatment, this book covers the development of mathematical descriptions and constitutive theories for deforming solids, fluids, and polymeric fluids---both compressible and incompressible with a clear distinction between Lagrangian and Eulerian descriptions as well as co- and contravariant bases. This thorough presentation of continuum mechanics shows how the subject is mathematically demanding with many involved derivations but very precise and rigorous.'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Continuum mechanics